A kind of water-free printing adhesive and preparation method thereof

Through controlled polymerization of macromolecular RAFT reagent, a water-free printing adhesive with a triblock copolymer structure was prepared, which solved the problems of poor color fastness and hard feel on polyester fabrics, achieved the combination of high color fastness and soft feel, and expanded the application range of water-free printing technology.

CN119332523BActive Publication Date: 2025-04-11HANGZHOU TRANSFAR FINE CHEM CO LTD +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411910588.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-04-11
Estimated Expiration
2044-12-24

AI Technical Summary

Technical Problem

The existing water-free printing adhesives have poor color fastness on polyester fabrics, a hard feel, and cannot reach the level of traditional water-washed printing fabrics, which limits its application range.

Method used

Controllable polymerization was performed using macromolecular RAFT reagent to prepare a water-free printing adhesive with a triblock copolymer structure. The adhesive consists of styrene, acrylate, acrylonitrile and silicone monomers. The emulsion and crosslinking are carried out through RAFT emulsion polymerization technology to form a block copolymer with two glass transition temperatures.

Benefits of technology

This adhesive not only improves the color fastness and color yield of the printed fabric, but also maintains the soft feel of the fabric. It is suitable for the water-free and dispersed dye printing process of polyester fabrics, expanding the application range of the water-free printing process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present invention provides a water-free printing adhesive and a preparation method thereof. The water-free printing adhesive is an emulsion obtained by polymerizing styrene, acrylate, acrylonitrile and silicone monomers as raw materials under the action of a macromolecular RAFT agent; the emulsion is: polystyrene-b-polyacrylate-b-poly(styrene- ran ‑Acrylonitrile‑ ran ‑organic silicon monomer) triblock copolymer. When the adhesive is used for polyester water-free disperse dye printing, it has better color fastness, the printed fabric has good softness, and can also obtain deep and bright colors.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials, and in particular relates to a water-free printing adhesive and a preparation method thereof. Background Art

[0002] The traditional disperse dye printing process is a printing technology mainly used for synthetic fiber fabrics. This process uses the good affinity of disperse dyes to fibers at high temperatures to bind the dyes to the fibers through high-temperature fixation. However, this process requires washing the fabrics after high-temperature fixation treatment to remove unfixed dyes and auxiliaries and improve color fastness, which leads to serious wastewater discharge problems, not only consuming a large amount of water resources, but also potentially polluting the environment due to the presence of chemical residues.

[0003] To solve this problem, the disperse dye wash-free printing process has emerged as a green printing and dyeing production technology, which meets the current requirements and trends of energy conservation and emission reduction. This process is to grind and disperse traditional powdered disperse dyes to make nano-scale liquid disperse dyes to improve the diffusion ability of dyes in fibers. However, compared with traditional methods, this process still has the problem of poor color fastness, so printing and dyeing factories usually implement it with printing adhesives. For example, 1) the printing adhesive is added to the dispersed color paste for joint printing; 2) the disperse dye is first printed on the surface of the fabric, and then the adhesive is used for padding and finishing after drying. However, method 1) has the problem of poor color fastness due to insufficient coverage of the disperse dye by the adhesive, and increasing the amount of adhesive will cause the print to feel hard; in method 2), the color fastness after adhesive padding is improved compared with method 1), but there is still a problem of obvious hardness. In practical applications, the color fastness and feel of the printed fabrics obtained by the above two methods do not reach the level of traditional disperse dye printing that requires washing. Therefore, the wash-free process can only be used for low-end fabric production, which limits its scope of application.

[0004] In this regard, patent CN 114163590 A provides a soft and non-sticky high color fastness paint printing adhesive, which aims to prepare a block polyacrylate emulsion through RAFT polymerization technology and compound it with a blocked isocyanate crosslinker to improve the color fastness of cotton fabric printing. However, the blocked isocyanate crosslinker in the adhesive cannot play a crosslinking role on polyester fabrics, resulting in poor friction / washing color fastness of the printing when it is applied to polyester fabrics.

[0005] Therefore, it is necessary to develop a water-free printing adhesive suitable for polyester fabrics, which has high color fastness, can maintain the soft feel of printed fabrics, and can effectively improve the color yield of printed fabrics. Summary of the invention

[0006] In order to overcome the problems of poor color fastness and hard hand feel of water-free printing adhesives on polyester fabrics in the prior art, the present invention provides a water-free printing adhesive particularly suitable for polyester fabrics and a preparation method thereof. The adhesive has good color fastness, and the prepared printed fabric has good soft hand feel and can obtain deep and bright colors.

[0007] The technical solution adopted by the present invention is: a water-free printing adhesive, wherein the water-free printing adhesive is an emulsion obtained by polymerization of styrene, acrylate, acrylonitrile and silicone monomers as raw materials under the action of a macromolecular RAFT agent; the emulsion is: polystyrene-b-polyacrylate-b-poly(styrene- ran -Acrylonitrile- ran -organic silicon monomer) triblock copolymer.

[0008] The present invention utilizes a macromolecular RAFT agent as the only emulsifier, and a controlled polymerization reaction is carried out by RAFT emulsion polymerization technology to prepare a water-free printing adhesive with a specific three-block structure. Due to the characteristics of the block structure, the adhesive has two glass transition temperatures, which can ensure the softness of the hand feel while improving the strength of the adhesive body, and the improvement of the strength of the adhesive body also helps to further improve its color fastness. Secondly, in the water-free printing adhesive, since the surface energy of the silicone monomer is low, it is easy to enrich on the surface of the film during the high-temperature baking process of the printing, which improves the hydrophobicity of the fabric and reduces the friction coefficient of the surface, which is beneficial to improve the dry and wet friction fastness of the fabric. At the same time, since the low-refractive index silicone is enriched into a film on the surface, the color yield of the printed fabric can also be improved. Therefore, the water-free printing adhesive is particularly suitable for the water-free disperse dye printing process for polyester fabrics.

[0009] Preferably, the raw materials include, by weight: 25-30 parts of acrylate, 10-15 parts of styrene, 0.5-3 parts of acrylonitrile, 1-3 parts of silicone monomer, 0.5-2 parts of macromolecular RAFT agent, 1-2 parts of alkaline solution, and 0.05-0.15 parts of initiator.

[0010] Preferably, the polystyrene-b-polyacrylate-b-poly(styrene- ran -Acrylonitrile- ran -organic silicon monomer) triblock copolymer has the structural formula: X-St n1 -b-nA n2 -b-(St- ran -CAN- ran -Si) n3 -R; where

[0011] X is derived from the dithioester group or trithioester group of the macromolecular RAFT agent, preferably an alkyl dithioester group or an alkyl trithioester group;

[0012] R is derived from the leaving group of the macromolecular RAFT agent, preferably one of isopropanoic acid, acetic acid, 2-nitroacetic acid, and 2-aminoacetic acid;

[0013] St is a styrene monomer unit, n1 is the average degree of polymerization of the polymer chain segment, n1 = 10-5000;

[0014] nA is an acrylate monomer unit, n2 is the average degree of polymerization of the nA polymer chain segment, n2 = 10-10000;

[0015] (St- ran -CAN- ran -Si) is a random copolymer of styrene, acrylonitrile and silicone monomers, n3 is (St- ran -CAN- ran -Si) The average degree of polymerization of the random copolymer, n3 = 10-5000.

[0016] Preferably, the acrylate is one of ethyl acrylate, butyl acrylate and isooctyl acrylate.

[0017] Preferably, the organic silicon monomer is one of vinyl silicone oil, methyl vinyl silicone oil and phenyl vinyl silicone oil.

[0018] Preferably, the organic silicon monomer accounts for 3%-8% of the total monomer mass, and the total monomers include styrene, acrylate, acrylonitrile, and organic silicon monomer. Experiments have shown that increasing the amount of organic silicon monomer can effectively improve the color yield of the fabric, but the color fastness of the printed fabric increases first and then decreases with the increase in the amount of organic silicon monomer. Therefore, the preferred amount of organic silicon monomer is 3%-8% of the total monomer mass, and more preferably 5%.

[0019] Preferably, the acrylonitrile accounts for 1%-5% of the total monomer mass, and the total monomers include styrene, acrylate, acrylonitrile, and silicone monomers. Experiments have shown that increasing the amount of acrylonitrile can effectively improve the color fastness of the fabric, and the improvement is about half a level, but further increasing the amount of acrylonitrile does not have a significant effect on improving the color fastness of the fabric, but instead causes the printed fabric to feel harder, so the preferred amount of acrylonitrile is 1%-5% of the total monomer mass, and more preferably 3%.

[0020] Preferably, the macromolecular RAFT agent is selected from amphiphilic macromolecular RAFT agents, such as polyacrylic acid-polystyrene RAFT agent (PAAm-PStn-RAFT), wherein the polymerization degrees m and n of polyacrylic acid and polystyrene can be adaptively adjusted.

[0021] The present invention also provides a method for preparing the water-free printing adhesive, comprising: dissolving a macromolecular RAFT agent in water, adding the macromolecular RAFT agent and part of styrene into a reactor, stirring and mixing, passing nitrogen until the air is completely replaced, heating to 70-90° C., adding a water-soluble initiator, initiating polymerization for 90-120 minutes, adding an alkaline solution and acrylate, polymerizing for 90-120 minutes, adding acrylonitrile, silicone monomer, and remaining styrene, polymerizing for 120-150 minutes, and post-treating the reaction solution to obtain the water-free printing adhesive.

[0022] Preferably, the post-treatment step comprises: adding an oxidant aqueous solution after cooling the reaction solution to 45-60°C, then slowly dripping an aqueous solution of a reducing agent over a period of 15-30 minutes, and then polymerizing for 30-60 minutes to obtain the water-free printing adhesive.

[0023] Preferably, the oxidant is selected from tert-butyl hydroperoxide; the reducing agent is selected from disodium glycolate sulfinate, dithiothreitol, dithioerythritol, and tri-(2-formylethyl)phosphine hydrochloride.

[0024] Preferably, the water-soluble initiator is one of persulfate, hydrogen peroxide and their derivatives.

[0025] The invention also provides application of the water-free printing adhesive in a water-free disperse dye printing process for polyester fabrics.

[0026] The beneficial effects of the present invention are as follows: the present invention uses RAFT agent as the only emulsifier to prepare a formaldehyde-free green environmentally friendly water-free printing adhesive through a controllable polymerization reaction, and the production process is simple and the production efficiency is high, which can further reduce the production cost. ran -Acrylonitrile- ran -organic silicon monomer) three-block structure emulsion, with two glass transition temperatures, which not only enhances the strength of the film, but also ensures the softness of the film, and achieves dual optimization of color fastness and feel. In addition, the adhesive does not contain an emulsifier, and the introduction of the organosilicon monomer in the third block significantly reduces the hydrophilicity of the film, thereby significantly improving the color fastness of the printed fabric and increasing the color yield of the fabric. The water-free printing adhesive provided by the present invention is particularly suitable for the water-free disperse dye printing process of polyester fabrics, which helps to expand the application range of the water-free printing process so that it can be applied to the production of high-end disperse printed fabrics. DETAILED DESCRIPTION

[0027] The following is an explanation of the embodiments of the present invention by specific specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied by other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that, in the absence of conflict, the features in the following embodiments and embodiments can be combined with each other. In the embodiments of the present invention, the methods used are all conventional methods unless otherwise specified, and the reagents used can be obtained from commercial sources.

[0028] The chemical structure of the macromolecular RAFT agent used in the embodiment of the present invention is:

[0029] .

[0030] Optionally, other commonly used amphiphilic macromolecular RAFT agents can also be used in the present invention, such as amphiphilic polymethacrylic acid-b-polymethyl methacrylate macromolecular RAFT agent (PMAA-b-PMMA-RAFT), amphiphilic polyacrylic acid-b-polystyrene macromolecular RAFT agent (AA-bS-RAFT), etc.

[0031] Example 1

[0032] 1.2 g of a macromolecular RAFT agent was dissolved in 4.8 g of water, and 4.2 g of styrene were added to a reactor, stirred and mixed, nitrogen was passed through for 20 minutes, and the temperature was raised to 80°C, and then 0.09 g of a water-soluble initiator was added. After initiating polymerization for 90 minutes, 1.2 g of ammonia water and 15.6 g of butyl acrylate were added, and polymerization was carried out for 90 minutes. Then 1.8 g of styrene, 1.2 g of acrylonitrile and 1.2 g of vinyl silicone oil were added, and polymerization was carried out for 2 hours. After the reaction solution was cooled to 50°C, tert-butyl hydroperoxide was added, and then disodium hydroxyacetic acid sulfinate was slowly added dropwise, and the addition was completed within 30 minutes. The polymerization reaction was continued for 60 minutes to obtain polystyrene-b-polyacrylate-b-poly(styrene- ran -Acrylonitrile- ran -organic silicone monomer) triblock copolymer of water-free printing adhesive A.

[0033] Example 2

[0034] 1.2 g of a macromolecular RAFT agent was dissolved in 4.8 g of water, and 4.2 g of styrene were added to a reactor, stirred and mixed, nitrogen was passed through for 20 minutes, and the temperature was raised to 80°C. Then, 0.09 g of a water-soluble initiator was added, and polymerization was initiated after 90 minutes. Then, 1.2 g of ammonia water and 16.2 g of butyl acrylate were added, and polymerization was carried out for 90 minutes. Then, 1.8 g of styrene, 1.2 g of acrylonitrile and 0.6 g of vinyl silicone oil were added, and polymerization was carried out for 2 hours. After the reaction solution was cooled to 50°C, tert-butyl hydroperoxide was added, and disodium hydroxyacetic acid sulfinate was slowly added dropwise, and the addition was completed within 30 minutes. Then, polymerization was carried out for 60 minutes to obtain polystyrene-b-polyacrylate-b-poly(styrene- ran -Acrylonitrile- ran -organic silicone monomer) triblock copolymer of water-free printing adhesive B.

[0035] Example 3

[0036] 1.2 g of a macromolecular RAFT agent was dissolved in 4.8 g of water, and 4.2 g of styrene were added to a reactor, stirred and mixed, nitrogen was passed through for 20 minutes, and the temperature was raised to 80°C, and then 0.09 g of a water-soluble initiator was added. After initiating polymerization for 90 minutes, 1.2 g of ammonia water and 15 g of butyl acrylate were added, and polymerization was carried out for 90 minutes. Then 1.8 g of styrene, 1.2 g of acrylonitrile and 1.8 g of vinyl silicone oil were added, and polymerization was carried out for 2 hours. After the reaction solution was cooled to 50°C, tert-butyl hydroperoxide was added, and then disodium hydroxyacetic acid sulfinate was slowly added dropwise, and the addition was completed within 30 minutes. The polymerization reaction was continued for 60 minutes to obtain polystyrene-b-polyacrylate-b-poly(styrene- ran -Acrylonitrile- ran -organic silicone monomer) triblock copolymer water-free printing adhesive C.

[0037] Example 4

[0038] 1.2 g of a macromolecular RAFT agent was dissolved in 4.8 g of water, and 4.2 g of styrene were added to a reactor, stirred and mixed, nitrogen was passed through for 20 minutes, and the temperature was raised to 80°C. Then, 0.09 g of a water-soluble initiator was added, and polymerization was initiated after 90 minutes. Then, 1.2 g of ammonia water and 16.5 g of butyl acrylate were added, and polymerization was carried out for 90 minutes. Then, 1.8 g of styrene, 0.3 g of acrylonitrile and 1.2 g of vinyl silicone oil were added, and polymerization was carried out for 2 hours. After the reaction solution was cooled to 50°C, tert-butyl hydroperoxide was added, and disodium hydroxyacetic acid sulfinate was slowly added dropwise, and the addition was completed within 30 minutes. Then, polymerization was carried out for 60 minutes to obtain polystyrene-b-polyacrylate-b-poly(styrene- ran -Acrylonitrile- ran -organic silicone monomer) triblock copolymer of water-free printing adhesive D.

[0039] Example 5

[0040] 1.2 g of a macromolecular RAFT agent was dissolved in 4.8 g of water, and 4.2 g of styrene were added to a reactor, stirred and mixed, nitrogen was passed through for 20 minutes, and the temperature was raised to 80°C. Then 0.09 g of a water-soluble initiator was added, and 1.2 g of ammonia water and 15 g of butyl acrylate were added after initiation of polymerization for 90 minutes. Then 1.8 g of styrene, 1.8 g of acrylonitrile and 1.2 g of vinyl silicone oil were added, and polymerization was carried out for 2 hours. After the reaction solution was cooled to 50°C, tert-butyl hydroperoxide was added, and disodium hydroxyacetic acid sulfinate was slowly added dropwise, and the addition was completed within 30 minutes. The polymerization reaction was continued for 60 minutes to obtain polystyrene-b-polyacrylate-b-poly(styrene- ran -Acrylonitrile- ran -organic silicone monomer) triblock copolymer of water-free printing adhesive E.

[0041] Example 6

[0042] 1.2 g of a macromolecular RAFT agent was dissolved in 4.8 g of water, and 4.2 g of styrene were added to a reactor, stirred and mixed, nitrogen was passed for 20 minutes, and the temperature was raised to 80°C. Then 0.09 g of a water-soluble initiator was added, and polymerization was initiated. After 90 minutes, 1.2 g of ammonia water and 15.6 g of butyl acrylate were added, and polymerization was carried out for 90 minutes. Then 1.8 g of styrene, 1.2 g of acrylonitrile and 1.2 g of vinyl silicone oil were added, and polymerization was carried out for 2 hours. The post-treatment step was omitted to obtain a polystyrene-b-polyacrylate-b-poly(styrene- ran -Acrylonitrile- ran -organic silicone monomer) triblock copolymer of water-free printing adhesive A1.

[0043] Comparative Example 1

[0044] 1.2 g of a macromolecular RAFT agent was dissolved in 4.8 g of water, and 4.2 g of styrene were added to a reactor, stirred and mixed, nitrogen was passed through for 20 minutes, the temperature was raised to 80° C., and 0.09 g of a water-soluble initiator was added. After initiating polymerization for 90 minutes, 1.2 g of ammonia water and 16.8 g of butyl acrylate were added, and polymerization was carried out for 90 minutes. Then, 1.8 g of styrene and 1.2 g of acrylonitrile were added, and polymerization was carried out for 2 hours. After the reaction solution was cooled to 50° C., tert-butyl hydroperoxide was added, and disodium glycolate sulfinate was slowly added dropwise, and the addition was completed within 30 minutes. The polymerization reaction was continued for 60 minutes to obtain a water-free printing adhesive F having a triblock copolymer of polystyrene-b-polyacrylate-b-poly(styrene-ran-acrylonitrile).

[0045] Comparative Example 2

[0046] 1.2 g of a macromolecular RAFT agent was dissolved in 4.8 g of water, and 4.2 g of styrene were added to a reactor, stirred and mixed, nitrogen was passed through for 20 minutes, and the temperature was raised to 80°C. Then 0.09 g of a water-soluble initiator was added, and 1.2 g of ammonia water and 14.4 g of butyl acrylate were added after initiation of polymerization for 90 minutes. Then 1.8 g of styrene, 1.2 g of acrylonitrile and 2.4 g of vinyl silicone oil were added, and polymerization was carried out for 2 hours. After the reaction solution was cooled to 50°C, tert-butyl hydroperoxide was added, and disodium hydroxyacetic acid sulfinate was slowly added dropwise, and the addition was completed within 30 minutes. The polymerization reaction was continued for 60 minutes to obtain polystyrene-b-polyacrylate-b-poly(styrene- ran -Acrylonitrile- ran -organic silicone monomer) triblock copolymer of water-free printing adhesive G.

[0047] Comparative Example 3

[0048] 1.2 g of a macromolecular RAFT agent was dissolved in 4.8 g of water, and 4.2 g of styrene were added to a reactor, stirred and mixed, nitrogen was passed through for 20 minutes, and the temperature was raised to 80°C, and then 0.09 g of a water-soluble initiator was added. After initiating polymerization for 90 minutes, 1.2 g of ammonia water and 16.8 g of butyl acrylate were added, and polymerization was carried out for 90 minutes. Then, 1.8 g of styrene and 1.2 g of vinyl silicone oil were added, and polymerization was carried out for 2 hours. After the reaction solution was cooled to 50°C, tert-butyl hydroperoxide was added, and then disodium hydroxyacetic acid sulfinate was slowly added dropwise, and the addition was completed within 30 minutes. The polymerization reaction was continued for 60 minutes to obtain polystyrene-b-polyacrylate-b-poly(styrene- ran -organic silicone monomer) triblock copolymer of water-free printing adhesive H.

[0049] Comparative Example 4

[0050] 1.2 g of a macromolecular RAFT agent was dissolved in 4.8 g of water, and 4.2 g of styrene were added to a reactor, stirred and mixed, nitrogen was passed through for 20 minutes, and the temperature was raised to 80°C, and then 0.09 g of a water-soluble initiator was added. After initiating polymerization for 90 minutes, 1.2 g of ammonia water and 13.8 g of butyl acrylate were added, and polymerization was carried out for 90 minutes. Then 1.8 g of styrene, 3 g of acrylonitrile and 1.2 g of vinyl silicone oil were added, and polymerization was carried out for 2 hours. After the reaction solution was cooled to 50°C, tert-butyl hydroperoxide was added, and then disodium hydroxyacetic acid sulfinate was slowly added dropwise, and the addition was completed within 30 minutes. The polymerization reaction was continued for 60 minutes to obtain polystyrene-b-polyacrylate-b-poly(styrene- ran -Acrylonitrile- ran -organic silicone monomer) triblock copolymer water-free printing adhesive I.

[0051] Application Examples

[0052] Adhesive AI prepared in Examples 1-5 and Comparative Examples 1-4 and a commercially available printing adhesive were added to disperse dye paste at a concentration of 15%, respectively, and water-free disperse dye printing was performed on polyester fabric. The printed fabric was tested for K / S value, color fastness to rubbing, color fastness to washing, and formaldehyde content (according to the definition of formaldehyde content in textiles in GB18401-2001). The results are shown in Table 1.

[0053] Fabric K / S value test: Use the American colorimeter Data color to determine the K / S value of polyester printed fabrics. Measure the K / S values ​​at five different positions on the front of the polyester printed fabric and take the average value.

[0054] Fabric color fastness to rubbing test: refer to GB-T3920-2008 "Textiles - Color fastness - Color fastness to rubbing" standard method test, use standard gray sample card to rate the fabric.

[0055] Fabric color fastness to washing test: refer to GB / T 3921-2008 "Textiles - Tests for color fastness - Color fastness to washing" test, use the standard grey sample card to evaluate the color fastness of the sample and the color fastness of the adjacent fabric.

[0056] Formaldehyde content determination: refer to GB18401 2001 "Limitations on formaldehyde content in textiles".

[0057] Table 1. Test results

[0058]

[0059] Note: Formaldehyde content less than 16PPM is recorded as undetectable; soap color fastness is 1-5 levels, 5 is the best and 1 is the worst.

[0060] As can be seen from Table 1, in Examples 1-3 and Comparative Examples 1-2, the mass ratio of the organic silicon monomer in the adhesive to the total monomer is different, namely 5%, 3%, 8%, 0%, and 10%, respectively. By comparison, it can be found that increasing the amount of organic silicon monomer can effectively improve the color yield of the fabric, but the color fastness of the printed fabric shows a trend of first increasing and then decreasing with the increase in the amount of organic silicon monomer. Therefore, the preferred amount of organic silicon monomer is 3%-8% of the total monomer, and more preferably 5%. In Examples 1, 4, 5 and Comparative Examples 3-4, the mass ratio of acrylonitrile in the adhesive to the total monomer is different, namely 3%, 1%, 5%, 0%, and 8%, respectively. By comparison, it can be found that increasing the amount of acrylonitrile can effectively improve the color fastness of the fabric, and the improvement is about half a level, but continuing to increase the amount of acrylonitrile does not have a significant effect on the improvement of the color fastness of the fabric, but instead causes the printed fabric to feel harder. Therefore, the preferred amount of acrylonitrile is 1%-5% of the total monomer, and more preferably 3%. Compared with Example 1, Example 6 omits the post-treatment step, and after residual monomer detection of the product, it is found that Adhesive A1 has more residual monomers than Adhesive A. Therefore, in the preparation process, post-treatment of the reaction solution with an oxidant / reducing agent can effectively improve the conversion rate of the monomers.

Claims

1. A water-free printing adhesive, characterized in that: The water-free printing adhesive is an emulsion obtained by polymerizing styrene, acrylate, acrylonitrile and silicone monomers under the action of a macromolecular RAFT agent; The emulsion is: polystyrene-b-polyacrylate-b-poly(styrene- ran -Acrylonitrile- ran -organic silicon monomer) triblock copolymer; The organosilicon monomer accounts for 3%-8% of the total monomer mass, the acrylonitrile accounts for 1%-5% of the total monomer mass, and the total monomers include styrene, acrylate, acrylonitrile, and organosilicon monomer.

2. The water-free printing adhesive according to claim 1, characterized in that: The raw materials include, by weight: 25-30 parts of acrylate, 10-15 parts of styrene, 0.5-3 parts of acrylonitrile, 1-3 parts of organosilicon monomer, 0.5-2 parts of macromolecular RAFT agent, 1-2 parts of alkaline solution, and 0.05-0.15 parts of initiator.

3. The water-free printing adhesive according to claim 1, characterized in that: The polystyrene-b-polyacrylate-b-poly(styrene- ran -Acrylonitrile- ran -organic silicon monomer) triblock copolymer has the structural formula: R-St n1 -b-nA n2 -b-(St- ran -CAN- ran -Si) n3 -X; in, X is derived from the dithioester group or trithioester group of the macromolecular RAFT agent; R comes from the leaving group of the macromolecular RAFT agent; St is a styrene monomer unit, n1 is the average degree of polymerization of the polymer chain segment, n1 = 10-5000; nA is an acrylate monomer unit, n2 is the average degree of polymerization of the nA polymer chain segment, n2 = 10-10000; (St- ran -CAN- ran -Si) is a random copolymer of styrene, acrylonitrile and silicone monomers, n3 is (St- ran -CAN- ran -Si) The average degree of polymerization of the random copolymer, n3 = 10-5000.

4. The water-free printing adhesive according to claim 1, characterized in that: The acrylic acid ester is one of ethyl acrylate, butyl acrylate and isooctyl acrylate.

5. The water-free printing adhesive according to claim 1, characterized in that: The organic silicon monomer is one of vinyl silicone oil, methyl vinyl silicone oil and phenyl vinyl silicone oil.

6. A method for preparing the water-free printing adhesive according to any one of claims 1 to 5, characterized in that: include: The macromolecular RAFT agent is dissolved in water, and added into a reactor together with part of styrene, stirred and mixed, nitrogen is introduced until the air is completely replaced, the temperature is raised to 70-90°C, a water-soluble initiator is added, and after initiating polymerization for 90-120 minutes, an alkali solution and acrylate are added, and polymerization is carried out for 90-120 minutes, and then acrylonitrile, silicone monomer and remaining styrene are added, and polymerization is carried out for 120-150 minutes. The reaction solution is post-treated to obtain the water-free printing adhesive.

7. The method according to claim 6, characterized in that The post-treatment step includes: adding an oxidant aqueous solution after the reaction solution is cooled to 45-60° C., then slowly dripping a reducing agent aqueous solution over a period of 15-30 minutes, and then polymerizing for 30-60 minutes to obtain the water-free printing adhesive.

8. Use of the water-free printing adhesive as described in any one of claims 1 to 5 in the water-free disperse dye printing process for polyester fabrics.

Citation Information

Patent Citations

  • Triblock copolymer tough resin latex and preparation method thereof

    CN114133500A

  • Method for sulphur-free soap-free in-situ raft emulsion copolymerisation of polymer / pigment hybrid latex

    WO2022052779A1